PENGARUH JUMLAH KATALIS DAN TEMPERATUR PADA PROSES PEMBUATAN BAHAN BAKAR CAIR LIMBAH STYROFOAM DENGAN METODE CATALYTIC CRACKING - ., Zurohaina; Zikri, Ahmad; Febriana, Ida; Amin, Jaksen M.; Pratiwi, Anggun; Pratiwi, Mitha; Reyhan, Muhammad Hifal (Politeknik Negeri Sriwijaya, 2020)
Styrofoam is a thermoplastic polymer that cannot be biodegradable. Styrofoam waste is generally treated using burning method which produce a dangerous gases. Cracking is the right method to solve the problem by converting styrofoam waste into liquid fuel. In this study, the cracking process was carried out by catalytic cracking method using zeolit alam, SiO2.Al2O3 dan Ï’-Al2O3 as a catalyst. The aims of this study are to determine the effect of the number of catalyst and temperature variation on the percentage of yield, physical properties and compound content of liquid fuel. Variabels varied are the number of catalyst 5-25% from total reactants and temperatur variation 300-550 oC. The result shows, the highest %yield using zeolit alam is 77,7846% at 20% catalyst, for silica alumina with variations of temperature showed the highest % yield in the temperature 450oC is 79,09% and for Ï’-Al2O3 with variations of temperature showed the highest % yield in the temperature 500oC is 68,20%